Does Song Effective for EFL Students’ Listening Skill?: (A Pre-Experimental Study at Junior High School Level) - Liando, Nihta V. F.; Oey, Nehemia A.; Rorimpandey, Rinny S. (Edumaspul: Jurnal Pendidikan, 2023)
Listening ability is one of the important language skills for students in understanding foreign languages. However, students often have difficulty in developing their listening skills. Therefore, the use of songs as a tool in foreign language learning has become popular among educators and researchers. This study aims to examine the effectiveness of using songs in improving students' listening skills. In this study, a quantitative method was applied through one group pre test and post test. In the study there were 25 students as samples in the study and each of them was in grade 9. The instrument used in collecting data is a test. The results of this study show that the use of song can effectively improve students' listening skills in English. This can be seen from the mean difference between pre test (57.8) and post test (81.6). The use of songs can improve students' listening comprehension and skills through several ways, such as improving vocabulary recognition skills, practicing context understanding, and increasing students' motivation and interest in foreign language learning. However, the effectiveness of using songs in foreign language learning depends on certain factors, such as the suitability of songs with learning objectives, the suitability of songs with students' ability levels, and the way of teaching carried out by teachers or instructors.